Embryo production and kids born through embryo transfer in Jakhrana goats treated with pFSH - GOEL, A K; KHARCHE, S D; JINDAL, S K; SINHA, N K (The Indian Journal of Animal Reproduction, 2023)
The present investigation was aimed to study the embryo production potential of Jakhrana goats and to know embryosurvivability in recipients. Goats were superovulated by using 16 mg pFSH (Sigma, USA) in reducing dose schedule over aperiod of3 days at 12 hours interval. Lutalyse (Dinoprost tromethamine, Upjohn, USA) and Crestar implant (lntervet, Holland)were used to synchronize oestrus. Ovarian response and embryo recovery averaged 9.40 ±2.53 and 5.20 ± 2.71, respectively.Twelve good quality embryos (4 to 16 cell stage) were surgically transferred in five oestrus synchronized recipients. Embryosurvivability was 42.00%. A total of five kids were born through embryo transfer.
Keywords: Goat; pFSH; embryo production and survivability; ET kids